O sigilo bancário brasileiro face à nova regulamentação americana Foreign Account Tax Compliance Act - FATCA - Holzmann, Deia Virginia Tidei (2016)
In light of the globalization we are facing a new reality of global interconnections which act as a central power transforming the international judicial relationships. Some countries have enacted regulations with extraterritorial effects as the Foreign Account Tax Compliance Act (FATCA), which establishes the sharing of information protected by bank secrecy which constitutes fundamental rights pursuant to the terms of the Brazilian Constitution. The proposal of the present work is to conduct an analysis of the Brazilian judicial system vis a vis the obligations established by the Foreign Account Tax Compliance Act (FATCA) in order to explore possible conflicts between the American regulation and the Brazilian laws with emphasis in the review of the fundamental rights guaranteed by the Brazilian Constitution. In the present work the topics covered are related to the historic and conceptual evolution of the bank secrecy and its insertion in the Brazilian law, the concept of the Foreign Account Tax Compliance Act (FATCA) and brief analysis of the Intergovernmental Cooperation Agreement (IGA) executed between Brazil and the United States of America, considerations on individual rights and guarantees protected by the Brazilian regulation and conclusion about the treatment of bank secrecy in Brazil